Pengendalian Kualitas Produk Banana Krezzz dengan Pendekatan Statistical Quality Control (SQC) di Kampoeng Banana Krezzz - Erlyna Wida Riptanti; Clarashinta Kusuma; Agustono Agustono (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Karanganyar Regency has excellent potential in the agricultural sector, particularly in banana commodities, which support processed industries such as Kampoeng Banana Krezzz, with its main product, banana krezzz. However, this company still experiences product damage and has not implemented a systematic quality control system, so the damage is not well-documented and risks compromising product quality. This study aims to identify the types of product defects, determine their repair priorities, establish the average control limits and variations in the production process, analyze the root causes and contributing factors of product defects, and formulate appropriate corrective actions. Data were collected through interviews, observations, and documentation over 30 days, and then analyzed using the Statistical Quality Control (SQC) approach, which included check sheets, Pareto charts, control charts, and fishbone diagrams. The results showed that the most dominant types of damage were inappropriate shape and size (68.39%) and skin damage (28.03%). The control chart analysis results indicate that the production process is not yet fully under statistical control, as evidenced by the presence of points outside the control limits. Fishbone chart analysis identified four primary causal factors of product damage: people, work methods, materials, and work environment. Proposed improvements include employee training, preparation of production SOPs, supervision of raw materials, and supervision of product quality.